DIGITAL TRAINING: TOWARDS A MULTIMODAL AND DIGITAL APPROACH TO CO-CONSTRUCTING LEARNING ENVIRONMENTS - Euphrosyne EFTHIMIADOU (Universitaria Publishing House, Craiova, 2022)
In the digital age, the socio-professional world is undergoing a transition period to move towards the development of digital skills of citizens, in order to reset education and training throughout life while respecting the personal rhythm of each participant. Under this aspect, it will be of prime interest to boost perceptions of cognitive and affective nature to release the creative potential of people in training. the implementation of innovative teaching methods focused on the good supervision and reciprocal online collaboration of trainees will allow them to invest effectively in the education and training process. Therefore, trainees will demonstrate digital abilities and transversal skills through the adoption of pedagogical strategies without neglecting the mastery of sophisticated digital tools, in order to react to the impasses of socio-professional life and to face the new challenges of the society of the future.